Influence of Si and Ge Microalloying Additions and Plastic Deformation on Precipitation Processes in Al-Cu Based Alloys - Castro Riglos, Maria Victoria (2018)
The combined effect of micro-alloying with Si and Ge and/or plastic deformationprior to ageing at 160˚C on age hardening has been studied in an Al-2 at%Cu alloy. The results obtained indicate that the hardness response is faster and the peak hardness is higher when plastic deformation and micro-alloying are applied together than performing each procedure individually. Different amounts of deformation, ranging from 0% to 30% have been utilized. An optimum deformation degree for the hardening response has been established around 8%for the Al-Cu-Si-Ge alloy. Characterization by transmission electron microscopy(TEM) shows that the peak hardness is due to a complex microstructurethat contained θ ′′ disc shaped precipitates, rod-shaped Si-Ge precipitatesand θ ′ plates that were heterogeneously nucleated on the Si-Ge particles.Pre-deformation has been found to stimulate the growth of the θ ′ platesdue to enhanced diffusion along dislocation cores. Increasing deformationreduces the influence of the Si-Ge precipitates on heterogeneous nucleation, leading to reduced peak hardness and faster over-ageing.